Neuromotor immaturity in children and adults : the INPP screening test for clinicians and health practitioners - Goddard, Sally, 1957- (Chichester, West Sussex, UK : John Wiley & Sons Ltd, 2014)
'Available to healthcare professionals for the first time, this book contains proven screening tests to measure neuromotor immaturity in children and adults in order to provide a basis for referral and help. Allows practitioners to screen for disorders of movement that can negatively affect educational performance and emotional function in children and adolescents. Assesses instances where disorders of movement in adults are affecting thoughts and behavior, as in panic disorder. Provides a novel approach for health care professionals observing aberrant reflexes in the absence of more serious pathology. Includes reproducible scoring and observation sheets for practice and serves as the perfect complement to Assessing Neuromotor Readiness for Learning'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Developmental Disabilities -- diagnosis; Movement disorders -- Diagnosis; Adult; Child; Mental disorders -- Etiology; Movement Disorders -- psychology; Developmental disabilities -- Diagnosis; Movement disorders -- Diagnosis